2016
DOI: 10.1111/jfpe.12494
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of modified atmosphere gases composition used for storage of high‐fiber muffins

Abstract: Four different dietary fibers were studied: oat fiber (AS), apple fiber (MD), carrot fiber (DC), and cocoa fiber (TC) and control sample. The muffins were produced to achieve more than 6 g/100 g of the final product. Each muffin with dietary fiber was packed in MAP with an initial gas mixture: 25% CO 2 , 50% CO 2 , 75% CO 2 , 100% CO 2 using nitrogen as an inert gas in MAP system. The quality of muffins was examined on the 1st and 15th day of packaging. We have observed that the firmness of the control sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In majority of studies, the authors showed the importance of a well-dimensioned packaging to preserve food and increase shelf life. The strategies proposed were (i) to correctly chose packaging regarding gas and water permeabilities to limit for example the oxidation (Rovira et al, 2019;Witik et al, 2019), or the water intake of dried products (Seth et al, 2018), (ii) use an optimal modified atmosphere to limit for example microbial spoilage (Chaix et al, 2015b;Guillard et al, 2016), quality loss of vegetables (Tsironi et al, 2017) or texture modification (Wyrwisz et al, 2017), and (iii) use an active packaging (ie packaging in which components were deliberately added to be liberated in food or headspace or to absorb a substance to increase the food shelf-life), as antimicrobial compounds (Ag, potassium sorbate etc.) to protect products from microbial growth (Marcuzzo et al, 2013;Apjok et al, 2019).…”
Section: Overview Of Current Modeling Of Shelf Lifementioning
confidence: 99%
“…In majority of studies, the authors showed the importance of a well-dimensioned packaging to preserve food and increase shelf life. The strategies proposed were (i) to correctly chose packaging regarding gas and water permeabilities to limit for example the oxidation (Rovira et al, 2019;Witik et al, 2019), or the water intake of dried products (Seth et al, 2018), (ii) use an optimal modified atmosphere to limit for example microbial spoilage (Chaix et al, 2015b;Guillard et al, 2016), quality loss of vegetables (Tsironi et al, 2017) or texture modification (Wyrwisz et al, 2017), and (iii) use an active packaging (ie packaging in which components were deliberately added to be liberated in food or headspace or to absorb a substance to increase the food shelf-life), as antimicrobial compounds (Ag, potassium sorbate etc.) to protect products from microbial growth (Marcuzzo et al, 2013;Apjok et al, 2019).…”
Section: Overview Of Current Modeling Of Shelf Lifementioning
confidence: 99%
“…Mechanical characteristics of bread in a double compression cycle were recorded in a Universal Testing Machine Instron 5965 (Instron, USA) with the maximal load of 500N, 50% penetration depth using a 40-mm diameter probe and a 20-s gap between compressions on the crumb cubes of 20 × 20 × 20 mm. The results were given as maximum level of firmness [N] and springiness of five samples from each batch of recipe and packaging [14].…”
Section: Texture Analysismentioning
confidence: 99%
“…Recent trends of bakery industry are contrary to the application of synthetic preservatives, and is more focused on the natural and neutral preservation techniques like MAP [13]. Moreover, the cost of fortified wheat bread roll is higher than regular bread and should have a longer shelf-life due to economic reasons which could be reached with the application of modified atmosphere packaging (MAP) [14]. Incorporation of dietary fibre means bread needs higher water content which could cause higher spoilage rates.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of a modified atmosphere includes atmospheric gases such as carbon dioxide, nitrogen and oxygen. Each of those gases has different properties, which makes them impact stored food in different ways (Wyrwisz et al., 2017). Modified atmosphere packaging, when using the right mix of gases, can extend bread's durability even up to 14–28 days.…”
Section: Introductionmentioning
confidence: 99%